Measurement Of Tremor In The Voices Of Speakers With Parkinson’s Disease - Marcus Bruckl; Alain Ghio (Al-Lisaniyyat)
A study is presented analyzing tremor in the voice of speakers that were diagnosed with Parkinson’s disease (PD). The examined sounds are sustained /a/s, originating from a large dysarthric speech corpus. Six measures of vocal tremor are extracted from these vowels by applying a self-developed algorithm that is based on autocorrelation of contours and implemented as a script of an open-source speech analysis program. Univariate analyses of covariance reveal significantly raised tremor magnitudes (tremor intensity indices and tremor power indices) in PD speakers off medication as compared to a control group as well as within PD speakers in off medication condition as compared to on medication. No significant differences are found between the control group and PD speakers on medication as well as for tremor frequencies. However, the greater part of variance in tremor measures is always accounted for the speakers’ age